Умный устойчивый город: опыт стран Северной Европы - Karagulian, E. A.; Batyreva, M. V.; Карагулян, Е. А.; Батырева, М. В. (Tyumen State University Herald. Social, Economic, and Law Research, 2020)
A review of the literature on the theory and practice of creating smart cities shows that there is no common understanding of the concept of a smart city, as well as the goals of its creation. The concept of a smart sustainable city has been gaining popularity in recent years and is being actively implemented in various countries. It is considered as a means of solving social, economic, and environmental problems caused by urbanization. The Nordic countries have achieved the greatest success in its implementation. The purpose of the article is to analyze the existing theories on the concept of smart sustainable cities, as well as the most successful experience of their creation in the Nordic countries. This analysis will allow us to determine the most optimal technologies for implementation in Russian practice. The methodological approach of this study includes a systematic review of the literature on smart cities, with an emphasis on those that focus on conceptual development and provide an empirical database. The review shows that the literature reveals three types of driving forces of smart sustainable cities. These are technologies, communities, and public policy which are associated with such areas of their development as improving the population welfare and the life quality in cities, productivity, and efficiency of their functioning and management. But this experience is not taken into account in the development of Russian programs for creating smart cities. The article presents a comprehensive study of the experience of Finland, Norway, Sweden, Denmark, and Iceland in creating smart sustainable cities, digitalizing the economy of countries, and at the same time in achieving the goals of sustainable development. Обзор литературы по теории и практике создания умных городов показывает, что единого понимания концепции умного города, а также целей его создания не существует. Концепция умного устойчивого города, набирающая в последние годы всё большую популярность и активно реализуемая в разных странах, ...